Product liability law: producer's liability for harmful cosmetic products - Roslan, Muhammad Azril; Abdul Aziz, Norazlina; Abd Rani, Ahmad Ridhwan; Roslan, Rosazra; Che Mohamad, Che Anuar (Secholian Publication, 2023)
Under relevant Malaysian laws, manufacturers or distributors who falsely claim that their cosmetics are safe are subject to criminal penalties. The question arises as to whether the producers can be responsible for physical as well as emotional injury caused to the consumers of such products. This paper seeks to investigate the potential liability of the manufacturer and distributor of defective cosmetics under the product liability law, which generally aims to protect consumers from unsafe products. The paper concentrates on the provisions of strict liability for defective products under Section X of the Consumer Protection Act 1999. The main issues to be resolved are whether cosmetics containing harmful substances can be considered as 'defective' and what kind of injury can be recovered by the victims. This study's findings provide producers and suppliers with information regarding their civil liability for supplying presumably safe cosmetics and the consumer's ability to obtain redress for harm caused by cosmetics comprising harmful ingredients.